Tudung Saji Business Implementation as an Effort to Improve Community Empowerment in Kota Lhokseumawe - Ti Aisyah; Amiruddin Ketaren; Syamsuddin Syamsuddin (Master Program of Sociology, Universitas Malikussaleh, 2023)
This study wants to explore how the implementation of the serving tudung business at Al Amin's creative house and the influence of the serving tudung craft business on community empowerment in Tumpok Teungoh village, Lhokseumawe city. This research is a descriptive qualitative research with data collection methods of observation, interviews and document study. The selection of the research location was carried out through a purposive sampling technique, which is a location for Community Empowerment in Tumpok Teungoh Village, Lhokseumawe City. Data analysts use interactive models, namely: data reduction, data presentation and drawing conclusions. The research results show thatthe serving hood craft business in Tumpok Teungoh Village has been implemented properly. This can be seen from the number of employees who have been hired, and sales that have been exported outside the city and the number of students who have succeeded in making this serving hood so that they can open their own craft business. This craft business can also help rural communities in terms of economy.